The exploratory study for the green neighbourhood initiative provision in Subang Jaya, Selangor, Malaysia / Rohana Ramli, Dasimah Omar and Puziah Ahmad - Ramli, Rohana; Omar, Dasimah; Ahmad, Puziah (2019)
This research reviews the findings from studies of exploratory for the green neighbourhood initiative provision in Subang Jaya. This stage is the starting point for determining the appropriate area to be selected for carrying out this study based on location, existing green neighborhood element, objectives and research approach. It is based on integrated physical planning that is expected to continue to develop not only can accommodate social need but, also can give benefit to economic and environmental. The aim of the study of exploratory is to get data and identify the existing green neighbourhood initiative provision, affected urban living development area within Subang Jaya, identify the location of a case study area, refine the research question and research approach in this study. The researcher chose to study the green neighbourhood initiative provision in the Subang Jaya area because it can give attractions, benefits and advantage of living in a particular urban area. At this stage, data collection was used in three ways, including document review, observation and interview. Five elements focused in this study are provided of pedestrian walkways, provision of bicycle lane, rainwater harvesting system, waste composting and community farming. In Subang Jaya it divided into 4 main areas and all the findings of green neighbourhood initiatives identified in each section which, total area for study area within 1,598,589 square meters. (2,122.7 acres). Discussion and conclusion of research had been made in this study.